The Gauge Integral Theory in HOL4 - Zhiping Shi; Weiqing Gu; Xiaojuan Li; Yong Guan; Shiwei Ye; Jie Zhang; Hongxing Wei (Journal of Applied Mathematics)
The integral is one of the most important foundations for modeling dynamical systems. The gauge integral is a generalization of the Riemann integral and the Lebesgue integral and applies to a much wider class of functions. In this paper, we formalize the operational properties which contain the linearity, monotonicity, integration by parts, the Cauchy-type integrability criterion, and other important theorems of the gauge integral in higher-order logic 4 (HOL4) and then use them to verify an inverting integrator. The formalized theorem library has been accepted by the HOL4 authority and will appear in HOL4 Kananaskis-9.